Amide group-containing lithium salt, preparation method thereof, electrolyte and lithium battery

CN122897787APending Publication Date: 2026-10-13UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611042102.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,随着截止电压的升高,正极材料在高压下会出现结构不稳定问题,表现为颗粒裂纹扩展、晶格相变加剧,进而诱发过渡金属离子溶出、晶格氧释放等一系列副反应

Benefits of technology

[0015]根据本发明上述实施例提供的含酰胺基锂盐,含酰胺基锂盐应用于锂电池的电解液中,含酰胺基锂盐中的酰胺基团可与锂离子紧密结合,降低有机溶剂对锂离子的配位能力,形成以阴离子为主的溶剂化结构。该含酰胺基锂盐的氧化分解电位较低,可在正极优先发生电化学分解,其含杂原子取代基的分解产物能够在正极形成内层含有氟化锂(LiF)等无机成分、外层为有机组分的稳定界面膜,抑制正极过渡金属催化的电解液持续分解副反应和正极层状材料的结构塌陷,从而保护正极材料,延缓高压条件下的容量衰减,提高电池循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897787A_ABST
    Figure CN122897787A_ABST
Patent Text Reader

Abstract

The application provides a lithium salt containing an amide group, a preparation method of the lithium salt, an electrolyte and a lithium battery, and belongs to the technical field of lithium batteries. The lithium salt containing the amide group has a structure as shown in formula (I): wherein R1, R2, R3, R4 and R5 are each independently selected from any one of a hydrogen atom, a halogen atom, a trifluoromethyl group, a nitro group, a cyano group, a fluorine-substituted or unsubstituted C1-C3 alkoxy group; and Z is selected from any one of a carbonyl group and an ester group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and in particular to an amide-containing lithium salt, its preparation method, electrolyte, and lithium battery. Background Technology

[0002] As an emerging strategic industry, the low-altitude economy has seen its market size continue to expand, becoming an important frontier for global technological and industrial competition. Its core carriers—electric vertical takeoff and landing aircraft (eVTOL) and drones—have placed higher performance demands on lithium batteries, which serve as the main power source: not only do they need higher energy density to extend range and increase payload capacity, but they must also ensure cost control, safety and reliability, and long cycle life.

[0003] Increasing the charging cutoff voltage of lithium-ion batteries can effectively unleash the capacity potential of cathode materials, bringing the actual discharge capacity closer to its theoretical value, which is an important way to achieve a leap in energy density. However, as the cutoff voltage increases, cathode materials exhibit structural instability under high voltage, manifested as particle crack propagation, intensified lattice phase transitions, and subsequently, a series of side reactions such as the dissolution of transition metal ions and the release of lattice oxygen. These structural degradation and interfacial side reactions together lead to rapid capacity decay and a significant reduction in cycle life, severely restricting the practical application and commercialization of high-voltage lithium-ion batteries. Summary of the Invention

[0004] In view of this, in order to at least partially solve the aforementioned technical problems, the present invention provides an amide-containing lithium salt, a method for preparing the same, an electrolyte, and a lithium battery.

[0005] According to one aspect of the present invention, an amide-containing lithium salt is provided, the amide-containing lithium salt having a structure as shown in formula (I):

[0006] Formula (I)

[0007] R1, R2, R3, R4, and R5 are each independently selected from any one of hydrogen atom, halogen atom, trifluoromethyl, nitro, cyano, fluorinated or unsubstituted C1~C3 alkoxy group; Z is selected from any one of carbonyl and ester groups.

[0008] According to another aspect of the present invention, a method for preparing an amide-containing lithium salt is provided, comprising:

[0009] Trifluoromethanesulfonamide was dissolved in acetonitrile. After complete dissolution, potassium carbonate was added, and the mixture was stirred at room temperature and placed in an ice bath to obtain the first solution.

[0010] An acyl chloride having the structure shown in formula (II) is dissolved in acetonitrile to form a homogeneous solution. The homogeneous solution is slowly added dropwise to the first solution, and the mixture is stirred at room temperature to obtain a mixture. The mixture is filtered, and the filtrate is rotary evaporated to obtain a potassium salt intermediate.

[0011] Equation (II)

[0012] The potassium salt intermediate and lithium perchlorate were dissolved in acetonitrile, respectively, and mixed and stirred at room temperature to carry out a displacement reaction. After filtration and precipitation, the filtrate was evaporated to obtain an amide-containing lithium salt.

[0013] According to another aspect of the present invention, an electrolyte is provided, comprising the above-described amide-containing lithium salt.

[0014] According to another aspect of the present invention, the present invention provides a lithium battery comprising the electrolyte described above.

[0015] According to the above embodiments of the present invention, the amide-containing lithium salt is applied in the electrolyte of a lithium battery. The amide group in the amide-containing lithium salt can tightly bind with lithium ions, reducing the coordination ability of organic solvents for lithium ions and forming a solvation structure dominated by anions. The amide-containing lithium salt has a low oxidation decomposition potential and can preferentially undergo electrochemical decomposition at the positive electrode. Its decomposition products containing heteroatom substituents can form a stable interfacial film at the positive electrode with an inner layer containing inorganic components such as lithium fluoride (LiF) and an outer layer of organic components. This film inhibits the continuous decomposition side reactions of the electrolyte catalyzed by the transition metal at the positive electrode and the structural collapse of the layered material of the positive electrode, thereby protecting the positive electrode material, delaying capacity decay under high voltage conditions, and improving the cycle stability of the battery. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings of the embodiments will be briefly described below. Obviously, the drawings described below only relate to some embodiments of the present invention and are not intended to limit the present invention.

[0017] Figure 1 Linear sweep voltammetry curves of Li||NCM811 batteries prepared in Example 1 and Comparative Example 1 of this invention;

[0018] Figure 2 The electrochemical impedance spectra of the Li||NCM811 batteries prepared in Example 1 and Comparative Example 1 of this invention are shown.

[0019] Figure 3 The cycling performance diagrams are for the Li||NCM811 batteries prepared in Example 5 and Comparative Example 4 of this invention, respectively.

[0020] Figure 4AX-ray photoelectron spectroscopy (XPS) of the interface composition of the Li||NCM811 battery prepared in Example 1 of this invention after cycling; and

[0021] Figure 4B The image shows the X-ray photoelectron spectrum of the interface composition after cycling of the Li||NCM811 battery prepared in Comparative Example 1 of this invention. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments and the accompanying drawings. However, this invention can be implemented in different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to make the invention thorough and complete, and to fully convey the scope of the invention to those skilled in the art. In the accompanying drawings, for clarity, the dimensions and relative dimensions of layers and regions may be exaggerated, and the same reference numerals denote the same elements throughout.

[0023] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. The terms “comprising,” “including,” etc., as used herein indicate the presence of the stated features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.

[0024] In related technologies, a nanoscale interface film, the cathode-electrolyte interphase (CEI), spontaneously forms between the cathode material and the electrolyte inside a lithium-ion battery. This interface layer acts as a physical and chemical barrier, directly regulating lithium-ion transport behavior, the rate of side reactions on the cathode surface, and profoundly affecting the battery's high-voltage stability and long cycle life. Research shows that a heterostructure CEI with an inner layer containing inorganic components such as lithium fluoride (LiF) and an outer layer of organic components possesses excellent mechanical strength and chemical inertness. It can effectively block direct contact between the highly active cathode material and the electrolyte, reduce side reactions at the cathode / electrolyte interface, and play a crucial protective role for the cathode.

[0025] The composition, structure, and stability of a CEI (Chemical Electrolyte Injector) are highly dependent on the chemical composition of the electrolyte. Using a large amount of highly fluorinated solvents can promote the formation of the inner LiF phase to some extent; for example, fluorinated silicone ethers are used as diluents in related technologies to broaden the battery's operating voltage and reduce side reactions. However, these solvents are typically expensive, have complex synthesis processes, and are highly environmentally toxic, limiting their large-scale industrial application. Therefore, introducing functional additives into the basic electrolyte system is considered a more feasible strategy for constructing efficient and stable CEIs. Currently, a large amount of research focuses on developing multifunctional additives, inducing the formation of organic-inorganic hybrid CEI films by introducing multiple functional groups through molecular design. For example, boron-containing additives can form low-impedance CEIs containing inorganic boron at the cathode, thereby comprehensively improving the mechanical strength and ion transport capacity of the interface layer.

[0026] However, the typical CEI structure derived from functional additives, consisting of an inner LiF layer and an outer organic phase, typically requires the oxidative decomposition of fluorine-containing functional groups in the additive. These fluorine-containing functional groups possess high bond energies, making electrochemical oxidative defluorination under normal battery operating conditions difficult. This hinders the efficient generation of the target LiF component, thus affecting the structural integrity and protective performance of the CEI. Therefore, a deep understanding of the defluorination reaction mechanism of fluorine-containing additives under high voltage, and the development of novel fluorine-containing additives that readily undergo electrochemical oxidative defluorination and can directionally construct the target CEI structure by adjusting the substituted functional groups in the molecular structure, can provide crucial interface control solutions for the development of high-energy-density, long-cycle-life high-voltage lithium batteries.

[0027] In view of this, the present invention provides an amide-containing lithium salt, its preparation method, an electrolyte, and a lithium battery.

[0028] According to an exemplary embodiment of the present invention, the present invention provides an amide-containing lithium salt having a structure as shown in formula (I):

[0029] Formula (I)

[0030] R1, R2, R3, R4, and R5 are each independently selected from any one of hydrogen atom, halogen atom, trifluoromethyl, nitro, cyano, fluorinated or unsubstituted C1~C3 alkoxy group; Z is selected from any one of carbonyl (C=O) and ester (-COO-).

[0031] In some embodiments, the halogen atom includes any one of fluorine, chlorine, bromine, and iodine atoms.

[0032] In some embodiments, the fluorinated or unsubstituted C1-C3 alkoxy group includes any one of methoxy, trifluoromethoxy, perfluoroethoxy, 2,2,3,3-tetrafluoropropoxy, and perfluoropropoxy.

[0033] In some embodiments, the structural formula of the amide-containing lithium salt includes one of the following:

[0034]

[0035] R3 is a trifluoromethoxy group;

[0036]

[0037] R2 and R4 are trifluoromethyl groups;

[0038]

[0039] R2 and R4 are nitro groups.

[0040] According to an exemplary embodiment of the present invention, the present invention provides a method for preparing an amide-containing lithium salt, comprising: operations S1 to S3.

[0041] In step S1, trifluoromethanesulfonamide is dissolved in acetonitrile. After complete dissolution, potassium carbonate is added, and the mixture is stirred at room temperature and placed in an ice bath to obtain the first solution.

[0042] In some embodiments, the molar ratio of trifluoromethanesulfonamide, acetonitrile, and potassium carbonate is 1:(11~20):(2~4), for example, it can be 1:11:2.5 or 1:20:3.7.

[0043] In embodiments of the present invention, the molar ratio of acetonitrile to trifluoromethanesulfonamide is greater than 11. By controlling the excess of acetonitrile, as much of the reactants and products as possible can be dissolved. The molar ratio of potassium carbonate to trifluoromethanesulfonamide is greater than 2. By controlling the excess of potassium carbonate, as much of the hydrogen on the trifluoromethanesulfonamide as possible can be removed, thereby enhancing the reactivity.

[0044] In operation S2, an acyl chloride having the structure shown in formula (II) is dissolved in acetonitrile to form a homogeneous solution. The homogeneous solution is slowly added dropwise to the first solution, and the mixture is stirred at room temperature to obtain a mixture. The mixture is filtered, and the filtrate is rotary evaporated to obtain a potassium salt intermediate.

[0045] Equation (II)

[0046] R1, R2, R3, R4, and R5 are each independently selected from any one of hydrogen atom, halogen atom, trifluoromethyl, nitro, cyano, or fluorinated or unsubstituted C1-C3 alkoxy group; Z is selected from any one of carbonyl and ester groups.

[0047] In embodiments of the present invention, the homogeneous solution is slowly added dropwise to the first solution in an ice bath at 0-4°C. In some embodiments, the molar ratio of acyl chloride to acetonitrile is 1:(2-5), for example, 1:2, 1:3, 1:3.4, 1:4, or 1:5, to ensure that the reactants are fully dissolved.

[0048] In step S3, the potassium salt intermediate and lithium perchlorate are dissolved separately in acetonitrile, mixed and stirred at room temperature to carry out a displacement reaction, and after filtration to precipitate, the filtrate is evaporated to obtain amide-based lithium salt. In the embodiments of the present invention, the molar ratio of potassium salt intermediate to lithium perchlorate is strictly 1:1 to avoid excess reactants that could lead to impure products.

[0049] According to an exemplary embodiment of the present invention, the present invention provides an electrolyte comprising the above-described amide-containing lithium salt.

[0050] In some embodiments, the mass fraction of the amide-containing lithium salt in the electrolyte is 0.4% to 80%, for example, it can be any value among 0.4%, 1%, 5%, 10%, 20%, 50%, and 80%. If the mass fraction of the amide-containing lithium salt in the electrolyte is too small (e.g., less than 0.4%), the amide-containing lithium salt will not be able to exert its effective function; if the mass fraction of the amide-containing lithium salt in the electrolyte is too large (e.g., greater than 80%), it will not be conducive to the dissolution of the amide-containing lithium salt in the electrolyte.

[0051] In some embodiments, the electrolyte of a lithium battery may also include at least one of other lithium salt electrolytes, organic solvents, and additives.

[0052] In some embodiments, other lithium salt electrolytes include at least one of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium bis(oxalate borate).

[0053] In some embodiments, the mass fraction of other lithium salt electrolytes in the electrolyte is 5% to 80%, for example, any value among 5%, 10%, 20%, 50%, 60%, 70%, and 80%.

[0054] In some embodiments, the organic solvent includes at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, methyl trifluoroethyl carbonate, and dimethoxyethane.

[0055] In some embodiments, the additive includes at least one of lithium difluorooxalate phosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, fluoroethylene carbonate, and methyltrifluoroethyl carbonate.

[0056] In some embodiments, the mass fraction of the additive in the electrolyte of the lithium battery is 0.5% to 50%, for example, it can be any value of 0.5%, 1%, 5%, 10%, 20%, 30%, 50%.

[0057] According to an exemplary embodiment of the present invention, the present invention provides a lithium battery comprising the above-mentioned electrolyte.

[0058] In some embodiments, the lithium battery further comprises a positive electrode, a negative electrode and a separator, and the separator is disposed between the positive electrode and the negative electrode.

[0059] In some embodiments, the positive electrode comprises at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganese oxide, lithium-rich manganese and ternary positive electrode materials, preferably a ternary positive electrode material. The ternary positive electrode material can be, for example, LiNi x Co y Mn 1-x-y O2, where 0<x<1, 0<y<1, and x+y<1.

[0060] In some embodiments, the negative electrode comprises at least one of lithium metal and graphite.

[0061] In some embodiments, the separator comprises at least one of a polyethylene-based separator, a polypropylene-based separator, and a polyolefin-based separator coated with lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LATP).

[0062] In the embodiments of the present invention, the amide group-containing lithium salt is applied to the electrolyte of a lithium battery. The amide group in the amide group-containing lithium salt can be tightly combined with lithium ions, reducing the coordination ability of the organic solvent to lithium ions, and forming an anion-dominated solvation structure. This amide group-containing lithium salt has a low oxidation decomposition potential, which can preferentially undergo electrochemical decomposition on the positive electrode. The decomposition product with a heteroatom substituent can form a stable interfacial film on the positive electrode, with an inner layer containing inorganic components such as lithium fluoride (LiF) and an outer layer being an organic component, which inhibits the side reaction of continuous electrolyte decomposition catalyzed by transition metals on the positive electrode and the structural collapse of the layered material of the positive electrode, thereby protecting the positive electrode material, delaying capacity attenuation under high-voltage conditions, and improving the cycle stability of the battery.

[0063] The designed amide group-containing lithium salt as well as its preparation method, electrolyte and lithium battery are described below by way of illustration. It should be noted that the illustrated examples are only specific embodiments of the present invention and do not limit the protection scope of the present invention.

[0064] The preparation conditions of the electrolyte in the following examples and comparative examples are as follows: the operation is carried out in an argon-filled glove box with a purity of 99.999%, the water content and oxygen content in the glove box are less than 0.01 ppm, and the temperature is room temperature.

[0065] Synthesis example 1

[0066] A lithium salt containing an amide group was synthesized, and the specific synthetic steps are as follows:

[0067] In step S1, dissolve 7.77g of trifluoromethanesulfonamide in 30mL of acetonitrile, add 18.00g of potassium carbonate, stir well at room temperature, and then place in an ice bath.

[0068] In step S2, 8.87 mL of trifluoromethoxybenzoyl chloride was separately dissolved in 10 mL of acetonitrile. After a homogeneous solution was formed, it was slowly added dropwise to the above ice bath solution and stirred overnight at room temperature. After the reaction, the resulting mixture was filtered, and the filtrate was rotary evaporated to obtain the potassium salt intermediate.

[0069] In step S3, 6.99 g of potassium salt intermediate and 1.98 g of lithium perchlorate were dissolved in acetonitrile, mixed and stirred at room temperature to carry out a displacement reaction. After filtration and precipitation, the solvent was removed by rotary evaporation of the filtrate to obtain amide-based lithium salt.

[0070] The NMR characterization data of the amide-based lithium salt obtained in Synthesis Example 1 are shown below:

[0071] 1 H NMR (400 MHz, DMSO-d6, ppm): δ 8.03-8.05 (d,2H), 7.35-7.37 (d,2H).

[0072] 19 F NMR (400 MHz, DMSO-d6, ppm): δ -56.74, -77.59.

[0073] Synthesis example 2

[0074] The amide-containing lithium salt was prepared using the same method as in Synthesis Example 1, except that trifluoromethoxybenzenesulfonyl chloride was replaced with an equimolar amount of 3,5-bis(trifluoromethyl)benzoyl chloride.

[0075] The NMR characterization data of the amide-based lithium salt obtained in Synthesis Example 2 are shown below:

[0076] 1 H NMR (400 MHz, DMSO-d6, ppm): δ 8.43 (d, 2H), 8.25 (m, 1H).

[0077] 19 F NMR (400 MHz, DMSO-d6, ppm): δ -61.43, -77.44.

[0078] Synthesis example 3

[0079] The amide-containing lithium salt was prepared using the same method as in Synthesis Example 1, except that trifluoromethoxybenzenesulfonyl chloride was replaced with an equimolar amount of 3,5-dinitrobenzoyl chloride.

[0080] The NMR characterization data of the amide-containing lithium salt of Synthetic Example 3 are shown below:

[0081] 1 H NMR (400 MHz, DMSO-d6, ppm): δ 8.93-8.94 (d, 2H), 8.90-8.91 (t, 1H).

[0082] 19 F NMR (400 MHz, DMSO-d6, ppm): δ -77.50.

[0083] Synthesis example 4

[0084] The amide-containing lithium salt was prepared using the same method as in Synthesis Example 1, except that the trifluoromethoxybenzenesulfonyl chloride was replaced with an equimolar amount of 4-nitrobenzene chloroformate.

[0085] The NMR characterization data of the amide-containing lithium salt obtained in Synthesis Example 4 are shown below:

[0086] 1 H NMR (400 MHz, DMSO-d6, ppm): δ 8.06-8.08 (m, 2H), 7.48-7.50 (dd, 2H).

[0087] Example 1

[0088] An electrolyte comprising the amide-containing lithium salt of Example 1 is provided, and its preparation process is as follows:

[0089] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 52 mg of the amide-based lithium salt obtained in Synthesis Example 1, 500 μL of ethylene carbonate / dimethyl carbonate (volume ratio 1:1) mixed solvent, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0090] Example 2

[0091] An electrolyte comprising the amide-containing lithium salt of Synthetic Example 2 is provided, and its preparation process is as follows:

[0092] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 60 mg of the amide-containing lithium salt from Synthesis Example 2, 500 μL of propylene carbonate, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to produce the electrolyte.

[0093] Example 3

[0094] An electrolyte comprising the amide-containing lithium salt of Synthetic Example 3 is provided, and its preparation process is as follows:

[0095] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 53 mg of the amide-containing lithium salt from Synthesis Example 3, 500 μL of propylene carbonate, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to produce the electrolyte.

[0096] Example 4

[0097] An electrolyte comprising the amide-containing lithium salt of Synthetic Example 1 is provided, and its preparation process is as follows:

[0098] In an argon-filled glove box, 94 mg of lithium difluorosulfonamide, 14 mg of lithium difluorooxalate borate, 52 mg of the amide-containing lithium salt obtained in Synthesis Example 1, and 500 μL of dimethoxyethane were taken and stirred until a homogeneous, clear, and transparent solution was obtained to produce the electrolyte.

[0099] Example 5

[0100] An electrolyte comprising the amide-containing lithium salt of Synthetic Example 1 is provided, and its preparation process is as follows:

[0101] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 52 mg of the amide-containing lithium salt obtained in Synthesis Example 1, 500 μL of a mixed solvent of ethylene carbonate / diethyl carbonate / methyl ethyl carbonate (volume ratio 1:1:1), and 25 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0102] Example 6

[0103] An electrolyte comprising the amide-containing lithium salt of Synthetic Example 4 is provided, and its preparation process is as follows:

[0104] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 48 mg of the amide-containing lithium salt from Synthesis Example 4, 500 μL of propylene carbonate, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to yield the electrolyte.

[0105] Comparative Example 1

[0106] An electrolyte is provided, and its preparation process is as follows:

[0107] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 500 μL of ethylene carbonate / dimethyl carbonate (volume ratio 1:1) mixed solvent, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0108] Comparative Example 2

[0109] An electrolyte is provided, and its preparation process is as follows:

[0110] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 500 μL of propylene carbonate, and 50 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0111] Comparative Example 3

[0112] An electrolyte is provided, and its preparation process is as follows:

[0113] In an argon-filled glove box, 94 mg of lithium difluorosulfonylimide, 14 mg of lithium difluorooxalate borate, and 500 μL of dimethoxyethane were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0114] Comparative Example 4

[0115] An electrolyte is provided, and its preparation process is as follows:

[0116] In an argon-filled glove box, 76 mg of lithium hexafluorophosphate, 14 mg of lithium difluorooxalate borate, 500 μL of a mixed solvent of ethylene carbonate / diethyl carbonate / methyl ethyl carbonate (volume ratio 1:1:1), and 25 μL of fluoroethylene carbonate were taken and stirred until a homogeneous, clear, and transparent solution was obtained to obtain the electrolyte.

[0117] The electrolytes obtained from the above embodiments and comparative examples were assembled into lithium batteries, and their cycle performance was tested as follows:

[0118] With LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) was used as the positive electrode, lithium foil as the negative electrode, and aluminum foil as the positive electrode current collector. The separator was a polyolefin separator coated with LATP. The battery was assembled in a glove box and tested after standing for 8 hours. The battery was activated by charging and discharging three times at a rate of 0.1C at a constant temperature of 30℃. Subsequently, it was charged and discharged at a rate of 1C, 2C, or 5C, with a cutoff voltage of 4.3V, 4.5V, 4.6V, or 4.7V. The capacity was tested, and the capacity retention rate was calculated. The results are shown in Table 1.

[0119] Table 1. Capacity and capacity retention of Li||NCM811 batteries after activation in the examples and comparative examples.

[0120]

[0121] Figure 1 Linear sweep voltammetry curves of Li||NCM811 batteries prepared in Example 1 and Comparative Example 1 of this invention are shown.

[0122] See Figure 1 As shown, the Li||NCM811 battery in Example 1 exhibits an oxidation peak at around 3.83 V, but does not undergo severe oxidation. This indicates that amide-containing lithium salts are preferentially oxidized and decomposed among the components of the electrolyte, thus proving that the difficulty of electrochemical oxidation is greatly reduced, which is conducive to their participation in the formation of the interface layer.

[0123] Figure 2 The images show the electrochemical impedance spectroscopy of the Li||NCM811 batteries prepared in Example 1 and Comparative Example 1 of this invention.

[0124] refer to Figure 2 As shown, compared with the Li||NCM811 battery of Comparative Example 1, the Li||NCM811 battery of Example 1 has lower interface resistance and charge transfer resistance, indicating that the interface layer formed by the degradation of amide-containing lithium salt has good ion transport performance.

[0125] Figure 3 The graphs show the cycle performance of the Li||NCM811 batteries prepared in Example 5 and Comparative Example 4 of this invention.

[0126] refer to Figure 3 As shown, when charged and discharged at 30°C, the capacity retention rate of the Li||NCM811 battery in Example 5 was significantly better than that of the Li||NCM811 battery in Comparative Example 4, indicating that the amide-containing lithium salt provided by the present invention can significantly improve the cycle stability of the battery and obtain a longer cycle life.

[0127] Figure 4A The X-ray photoelectron spectrum of the interface composition after cycling of the Li||NCM811 battery prepared in Example 1 of this invention.

[0128] Figure 4B The image shows the X-ray photoelectron spectrum of the interface composition after cycling of the Li||NCM811 battery prepared in Comparative Example 1 of this invention.

[0129] refer to Figure 4A , Figure 4BAs shown, in Example 1, the LiF content in the inner layer of the interface layer formed on the positive electrode is higher than that in Comparative Example 1. This indicates that Example 1 formed an interface layer with an outer layer dominated by organic components and an inner layer dominated by inorganic LiF components. This type of interface layer is recognized as a high-performance positive electrode protective layer. The above data demonstrates that amide-containing lithium salts have a low oxidation decomposition potential and can preferentially degrade on the positive electrode, generating a stable protective layer with an inner layer rich in LiF and an outer layer dominated by organic phases. This protects the positive electrode material, delays capacity decay under high voltage, and improves battery cycle performance.

[0130] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A lithium salt containing an amide group, characterized in that, The amide-containing lithium salt has the structure shown in formula (I): Equation (I) R1, R2, R3, R4, and R5 are each independently selected from any one of hydrogen atom, halogen atom, trifluoromethyl, nitro, cyano, fluorine-substituted or unsubstituted C1~C3 alkoxy group; Z is selected from either carbonyl or ester groups.

2. The amide-containing lithium salt according to claim 1, characterized in that, Halogen atoms include any one of fluorine, chlorine, bromine, and iodine atoms; Fluorine-substituted or unsubstituted C1-C3 alkoxy groups include any one of methoxy, trifluoromethoxy, perfluoroethoxy, 2,2,3,3-tetrafluoropropoxy, and perfluoropropoxy.

3. The amide-containing lithium salt according to claim 1, characterized in that, The structural formula of the amide-containing lithium salt includes one of the following: R3 is a trifluoromethoxy group; R2 and R4 are trifluoromethyl groups; R2 and R4 are nitro groups.

4. A method for preparing an amide-containing lithium salt as described in any one of claims 1 to 3, characterized in that, include: Trifluoromethanesulfonamide was dissolved in acetonitrile. After complete dissolution, potassium carbonate was added, and the mixture was stirred at room temperature and placed in an ice bath to obtain the first solution. An acyl chloride having the structure shown in formula (II) is dissolved in acetonitrile to form a homogeneous solution. The homogeneous solution is slowly added dropwise to the first solution, and the mixture is stirred at room temperature to obtain a mixture. The mixture is filtered, and the filtrate is rotary evaporated to obtain a potassium salt intermediate. Equation (II) The potassium salt intermediate and lithium perchlorate were dissolved in acetonitrile, respectively, and mixed and stirred at room temperature to carry out a displacement reaction. After filtration and precipitation, the filtrate was evaporated to obtain the amide-containing lithium salt.

5. An electrolyte, characterized in that, Including the amide-containing lithium salt as described in any one of claims 1 to 3.

6. The electrolyte according to claim 5, characterized in that, The mass fraction of the amide-containing lithium salt in the electrolyte is 0.4% to 80%.

7. The electrolyte according to claim 5, characterized in that, The electrolyte also includes at least one of other lithium salt electrolytes, organic solvents, and additives.

8. The electrolyte according to claim 7, characterized in that, The other lithium salt electrolytes include one or more of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, and lithium bis(oxalate borate). Preferably, the organic solvent includes one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate, methyl trifluoroethyl carbonate, and dimethoxyethane. Preferably, the additive includes one or more of lithium difluorooxalate phosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium perchlorate, fluoroethylene carbonate, and methyltrifluoroethyl carbonate.

9. A lithium battery, characterized in that, Includes the electrolyte as described in any one of claims 5 to 8.

10. The lithium battery according to claim 9, characterized in that, It also includes a positive electrode, a negative electrode, and a separator, wherein the separator is disposed between the positive electrode and the negative electrode. Preferably, the positive electrode comprises at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese, and ternary positive electrode materials; The negative electrode includes at least one of lithium metal and graphite; Preferably, the diaphragm includes at least one of polyethylene diaphragms, polypropylene diaphragms, and polyolefin diaphragms with a lithium titanium aluminum phosphate coating.